The littlest dinosaur's big adventure - Foreman, Michael, 1938- (New York : Walker & Co., 2009)
The littlest dinosaur discovers the advantages of being small as he frolics among the lily pads with his new frog friends, and then bravely finds his way home after getting lost in the woods.
Kirkus Review.
2.8
K-3
Keywords: Dinosaurs -- Juvenile fiction; Missing children -- Juvenile fiction; Perception -- Juvenile fiction; Dinosaurs -- Fiction; Lost children -- Fiction; Size -- Fiction; Dinosaurs -- Fiction; Missing children -- Fiction; Size -- Fiction